Sardinian composers of contemporary music - Giglio, Consuelo (Interdisciplinary Studies in Musicology, 2018)
The meeting point between the school headed by Franco Oppo and the rich traditional music of the island gave birth in Sardinia to an intense flowering in the field of New Music, with a strong feeling of belonging and a constant call for a positive concept of identity. Thus, since the time of Oppo (1935) and his contemporary Vittorio Montis, we come across many composers that differ between each other but are almost always recognizably “Sardinian”. Oppo has been one of the most interesting figures on the international scene during the last few decades. After his studies in Rome, Venice and Poland in the early 1960s, he remained, by his own choice, in his home territory, sharing his “Sardinian-ness” in a free and dialectic manner with the avant-garde. After formulating his own particular aleatory approach, Oppo reached a turning point halfway through the 1970s: in Musica per chitarra e quartetto d’archi, Praxodia and, finally, in Anninnia I, the meeting point between avant-garde research and the special phonic quality of traditional music became more and more close-knit and organic, at the same time also acting on the founding language structure whilst still remaining under the control of incisive and informed disciplines (during the same period, moreover, he put forward new methodologies of analysis which were also necessary for his teaching). In this sense the most important works are chamber pieces like Anninnia I and II (1978, 1982), Attitidu (1983) and Sagra (1985), the theatrical work Eleonora d’Arborea (1986), some piano “transcriptions” - the Three berceuses (1982), Gallurese and Baroniese (1989; 1993) - Trio III (1994), Sonata B for percussion and piano (2005) and the two Concerts for piano and orchestra (1995-97; 2002). Meanwhile, the foundation of a new Sardinian musical culture was also placed within the social context too, with Oppo’s deep personal engagement. At first Oppo promoted the Giornate di musica contemporanea (1977-1978), a weighty international festival, inside the Teatro Lirico of Cagliari, later founding, with some of his students, the Festival Spaziomusica (1982). Still an active event, the latter has proved to be a solid structure thanks to which generations of Sardinian composers have been able to promote their music alongside the most famous names of the avant-garde, with also the opportunity of several important conferences. From the earliest days much attention was paid to Scelsi, and, with the backdrop of the presence of Nono, Xenakis and Stockhausen, electronic music also continues to maintain a very active profile on the island. Moreover, three research centres conceived in 1990 by some of Oppo’s students have been veiy active: Spaziomusica Ricerca, Ricercare and the CERM of Sassari, which in 1992 brought the Sardinian experience to the 36. Ferienkurse fur Neue Musik. Fabrizio Casti, Antonio Doro, Lucio Garau, Marcello Pusceddu and Giorgio Tedde, together with the younger Ettore Carta and Andrea Saba, who started writing in the 1980s, can be identified as the first and most interesting generation of musicians who grew up studying with Oppo at the Conservatory of Cagliari, while Antonio Lai, the last of his students, specialized in theoretical research, working in Paris.